The other talk : reckoning with our white privilege - Kiely, Brendan, 1977- (Atheneum, 2021)
"Most kids of color grow up talking about racism. They have "The Talk" with their families-the honest talk about survival in a racist world. But white kids don't. They're barely spoken to about race at all-and that needs to change. Because not talking about racism doesn't make it go away. Not talking about white privilege doesn't mean it doesn't exist. The Other Talk begins this much-needed conversation for white kids. In an instantly readable and deeply honest account of his own life, Brendan Kiely offers young readers a way to understand one's own white privilege and why allyship is so vital, so that we can all start doing our part-today"--